KONTEKSTUALISASI NILAI-NILAI TAFAQQUH FI AD-DIN DALAM IMPLEMENTASI PENDIDIKAN ANTI BULLYING DI PESANTREN - Januri (Institut Agama Islam Yasni Bungo, 2026)
This study aims to contextualize the values of tafaqquh fi ad-din in the implementation of anti-bullying education at Al-Muballighin Islamic Boarding School, Muara Bungo. Bullying phenomena, manifested in verbal, physical, and psychological forms, are still found within the pesantren environment, despite its reputation as a religious-based educational institution that emphasizes moral and character development. The values of tafaqquh fi ad-din, which focus on deepening religious understanding and internalizing Islamic moral values, are believed to have strong potential as a foundation for building a comprehensive anti-bullying culture. This study employs a qualitative case study approach. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, with data reduction, data display, and conclusion drawing, and triangulation was used to ensure data validity. The findings indicate that bullying persists due to a lack of supervision, imbalanced senior-junior relationships, and insufficient internalization of religious values in students’ daily practices. The values of tafaqquh fi ad-din, such as proper conduct (adab), empathy, mutual respect, and the prohibition of harming others, are highly relevant as foundational principles for anti-bullying education. Contextualization strategies were implemented through strengthening the moral education curriculum, habituation of Islamic behavior, role modeling by caregivers, and the integration of religion-based anti-bullying policies. The implementation of these values has proven effective in fostering a safer and more inclusive pesantren environment that reflects the principles of compassion and respect. This study offers both theoretical and practical contributions by proposing a tafaqquh fi ad-din based anti-bullying education model that can be applied in other Islamic boarding schools.